Investigation of fungal flora in hammams, Turkish baths: A field study - Savcı, Ünsal; Şahin, Mustafa (Journal of Surgery and Medicine, 2019)
Aim: Hammams, also known as Turkish Hammams or Turkish Baths, have preserved their traditional importance and popularity in various countries, namely, Turkey, Morocco, Yemen, and Algeria. In this study, we aimed to evaluate the fungal flora in hammams and its effects on public health. Methods: This cross-sectional study was performed by collecting two hundred forty samples from different areas of the baths and the tools used. Collected samples were inoculated on Sabouraund dextrose agar and Potato dextrose agar for mycological evaluation. Agar plates were incubated at 25 °C and 37 °C for four weeks and fungal growth was observed every day. For identification of isolated fungi, micro and macro morphology was evaluated; germ tube test, biochemical tests and VITEK®2 Compact (Biomerieux, France) equipment were used. Results: We determined that molds are the most common fungi in Turkish hammams. Aspergillus spp. (n=20), Scedosporium apiospermum/boydii (n=5), Alternaria ulocladium (n=1), Rhizomucor spp. (n=1) and Penicillium spp. (n=1) were isolated in collected samples. Isolated yeasts were Trichosporon spp. (n=6), Candida albicans (n=1) and Candida tropicalis (n=1). Trichophyton tonsurans, the dermatophyte, was isolated in two samples. Fungus was most commonly isolated from slippers, and not at all isolated from towels or peshtemals. Conclusion: In our study, the most isolated molds were fungi, found in the nature, and the isolation rate was exceptionally low. Dermatophytes are the most common culprit of fungal transmission in public places such as baths. Compared to previous studies conducted in swimming pools, wrestling cushions, mosque carpets and slippers, our study showed that Turkish baths with high humidity and temperatures are not rich in fungal flora and that the risk of fungal contamination is low.